Timing and distribution of attack by the banana weevil (Coleoptera: curculionidae) in East African highland banana (Musa spp.) - Abera, A.M.K.; Gold, Cliford S.; Kyamanywa, S. (1999)
Timing and distribution of attack on East African highland banana (Musa AAA- EA) by the banana weevil, Cosmopolites sordidus (Germar), (Coleoptera: Curculion- idae) was studied in a field trial at a farm 25 km NE of Kampala, Uganda. Weevils were released at three densities (5, 20 and 40 females per mat) in 324 m' banana plots (cv Atwalira) that had been established 18 months earlier and maintained relatively free of weevils. Two weeks after release, entire mats were removed and examined for weevil eggs and first instar larvae. At a density of 20 weevils per mat, oviposition occurred on 25% of plants less than 6 six months old (suckers) with an average of three eggs (range 0-16) per infested plant. At the same time, 85% of flowered plants were at- tacked with mean oviposition of 15 eggs (range 0-41) per plant. An inverse relation- ship existed between weevil population density and eggs/female/plant. Five females per mat produced an average of 7.2 eggs per flowered plant, whereas 20 females pro- duced 15 eggs per flowered plant and 40 females produced 12.5 eggs. This suggests the existence of density-dependent factors in weevil oviposition. Over 90% of the oviposi- tion occurred in the base of the pseudostem, with the remaining eggs found in the corm and roots near the soil surface. However, in stands displaying high mat, (a con- dition in which part of the corm appears above the soil surface) more eggs were found on the corm than pseudostem.